2013
DOI: 10.1289/ehp.1206198
|View full text |Cite
|
Sign up to set email alerts
|

Sulfated Metabolites of Polychlorinated Biphenyls Are High-Affinity Ligands for the Thyroid Hormone Transport Protein Transthyretin

Abstract: Background: The displacement of l-thyroxine (T4) from binding sites on transthyretin (TTR) is considered a significant contributing mechanism in polychlorinated biphenyl (PCB)-induced thyroid disruption. Previous research has discovered hydroxylated PCB metabolites (OH-PCBs) as high-affinity ligands for TTR, but the binding potential of conjugated PCB metabolites such as PCB sulfates has not been explored.Objectives: We evaluated the binding of five lower-chlorinated PCB sulfates to human TTR and compared thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
151
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(154 citation statements)
references
References 49 publications
2
151
1
Order By: Relevance
“…The lower logK ow value leads to much easier root-to-shoot translocation of 6-OH-BDE-47 than those of BDE-47 and 6-MeO-BDE-47. A reasonable explanation is that the presence of the hydroxy group in 6-OH-BDE-47 increases its polarity and water solubility and renders it more prone to transfer from roots to shoots than either the corresponding unsubstituted BDE-47 or 6-MeO-BDE-47 (Grimm et al, 2013;Li et al, 2011;Malmv€ arn et al, 2008;Su et al, 2014). Studies have confirmed that OH-PBDEs have higher toxicity than their parent PBDEs and corresponding MeO-PBDEs (Xu et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The lower logK ow value leads to much easier root-to-shoot translocation of 6-OH-BDE-47 than those of BDE-47 and 6-MeO-BDE-47. A reasonable explanation is that the presence of the hydroxy group in 6-OH-BDE-47 increases its polarity and water solubility and renders it more prone to transfer from roots to shoots than either the corresponding unsubstituted BDE-47 or 6-MeO-BDE-47 (Grimm et al, 2013;Li et al, 2011;Malmv€ arn et al, 2008;Su et al, 2014). Studies have confirmed that OH-PBDEs have higher toxicity than their parent PBDEs and corresponding MeO-PBDEs (Xu et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The lower chlorinated OHPCBs have also been shown to interact with cytosolic sulfotransferases (SULTs) that are active in metabolism of steroid hormones [16] and thyroid hormones [17]. Moreover, OHPCBs [18, 19] as well as the products of sulfation of OHPCBs [20] have been shown to bind with high affinity to the thyroid hormone transport protein transthyretin. These interactions of OHPCBs with sulfotransferases involved in the metabolism of steroid hormones and with thyroid hormone carriers may contribute to the endocrine disruption observed with some PCBs [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, results reported by many authors (Crofton & Zoeller 2005, Miller et al 2009, Patrick 2009, Grimm et al 2013 indicate the following mechanisms to be involved in the impairment of thyroid function by PCBs: i) PCBs may reduce the ability of THs to bind to the transport proteins (transthyretin) in the bloodstream; ii) PCBs may impair the proteolysis of thyroglobulin; iii) PCBs may activate the aryl hydrocarbon receptors (AhRs), resulting in the elevation of the concentrations of several hepatic enzymes, including uridine diphosphate glucuronyl transferases and sulfotransferases; iv) PCBs may activate phase II conjugation of T 4 (formation of T 4 -glucuronide (T 4 -G)), resulting in the elevation of biliary excretion of T 4 -G and reduction in the circulating concentration of T 4 , leading to hypothyroidism; v) PCBs may inhibit or upregulate the production of deiodinases that allow T 4 to be converted to T 3 ; and vi) PCBs may act as either an agonist or an antagonist at the site of the cellular TR, where they induce a partial dissociation of TR/retinoid X receptor (RXR) heterodimer complex from the TRE, resulting in the suppression of gene transcription. Although it is not clear which among these potential mechanisms are most important for mediating the effects of PCBs on the circulating concentrations of THs, it is likely that all are important to some extent in experimental models.…”
Section: Discussionmentioning
confidence: 67%
“…Polychlorinated biphenyls (PCBs), a xenobiotic group of halogenated aromatic hydrocarbons, are the most hazardous, widespread, persistent, and ubiquitous environmental contaminants (Persky et al 2012, Grimm et al 2013, Murk et al 2013. A large number of PCB congeners, about 209 PCBs, are produced and used in industrial materials and domestic products worldwide (Zoeller et al 2002), and their toxicological properties depend on the number and position of chlorine substitutions (Leijs et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation